Are categorical deniers different? Understanding demographic, personality, and psychological differences between denying and admitting individuals with sexual convictions - Ware, Jayson (Deviant behavior, 2020)
The purpose of this study was to establish whether there were demographic, personality, or psychological differences between a sample of 40 incarcerated sex offenders in categorical denial and 37 sex offenders admitting responsibility in an Australian minimum-security unit. Categorical deniers had lower IQs, were older, and were more likely to be child molesters. Criminogenically, there were no differences between categorical deniers and those who admitted their offences in relation to Static-99 risk scores. Psychologically, offenders denying their offences were significantly more shame-prone, and likely to use externalization as a method of impression-management. They were also more compulsive than those admitting their offences, but less antisocial and sadistic, when compared on personality indices. The study is limited by the small sample size however implications for further research and the treatment of categorical deniers are discussed.